2007
DOI: 10.1002/lsm.20514
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nd:YAG laser‐mediated thermal damage in rabbit nasal septal cartilage

Abstract: These results demonstrate that significant thermal damage is concurrent with clinically relevant shape change. This contradicts previous notions that there is a privileged laser dosimetry parameter where clinically relevant shape change and tissue viability coexist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Thermography was also used to follow temperature rise during laser exposures of cartilage material at powers consistent with clinical reshaping. 14 In that study, fluorescence damage detection using confocal microscopy identified regions of dead chondrocytes but there was no correlation between temperature history and threshold cellular death.…”
Section: Introductionmentioning
confidence: 79%
“…Thermography was also used to follow temperature rise during laser exposures of cartilage material at powers consistent with clinical reshaping. 14 In that study, fluorescence damage detection using confocal microscopy identified regions of dead chondrocytes but there was no correlation between temperature history and threshold cellular death.…”
Section: Introductionmentioning
confidence: 79%
“…Regardless of the precise mechanism of action, a major concern with LCR focuses on the potential thermal injury to the chondrocytes during photothermal heating. While temperature dependent thermal injury has been studied using many different laser and other heating systems in ex vivo animal cartilages [59], no studies have systematically evaluated the effects of laser dosimetry on human nasal septal cartilage. This information is critically important, especially if LCR is to gain broader clinical acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques can be used to assess chondrocyte viability [10,11], however gauging acute thermal injury may be best accomplished using a Live/Dead viability assay system combined with laser confocal microscopy [1215]. Recent studies on laser mediated shape change and resultant tissue viability using the Live/Dead assay approach demonstrated that significant thermal damage is concurrent with clinically relevant shape change on animal septal cartilage [79]. These studies are at variance with previous hypothesis that there is a privileged laser dosimetry parameter where clinically relevant shape change and tissue viability coexist.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of cooling materials have been used such as cryogen spray [17]. The purpose of this cold water is to prevent overheating of the cartilage as this thermal injury is inevitable in some author's opinion [18]. Brian Wong and his team studied this thermal effect and observed a direct relationship between laser dosimetry and tissue damage [19].…”
Section: -Discussionmentioning
confidence: 99%